Title of the Ancient Türks: “Kagan” (Qagan) and “Zhabgu” (Yabgu) - Karataev, O. (al-Farabi Kazakh National University, 2020)
The Turks managed to create a huge empire. Territory – from the Altai mountains in the east to theBlack Sea in the west, from the upper Yenisei in the north to the upper Amu Darya in the south. At thebeginning of the VI century, the territory of Kazakhstan came under the authority of the Turkic Kaganate.Turkic Kaganate is the first state in Kazakhstan. Its basis was the union of Turkic-speaking tribes, whichwas headed by the kagan. The state, based on tribal traditions, was based on military-administrativemanagement. It was part of a system of relations with such major states of the time as Iran and Byzantium.China was a tributary of the kaganate. The title in many cultures played the role of an importantindicator of the international prestige of the state. As is known, only members of the Ashin clan had thesacred right to supreme power in the Turkic Kaganate. Possession of one or another title, occupation ofone or another place in the political and state structure of society, depended on many circumstances,the main of which was belonging to a particular tribe in a tribal union, clan in a tribe, etc. Social determinants(titles, ranks, positions), as the most significant components of ancient Turkic anthroponomy,contained complete information about the social status of the bearer of a given name, its origin andmembership in a particular layer of society, data on its place in the political structure of society andthe administrative structure . The political and military organization of Turkic society in many respectscontinued the traditions of previous state formations of the Huns. In linguistic terms, most of them areborrowings – mainly from Sogdian, Chinese and Tibetan languages.